Detection of OFDM modulations based on the characterization in the phase diagram domain - Digulescu, Angela; Sârbu, Annamaria; Stanescu, Denis; Nastasiu, Dragoș; Despina-Stoian, Cristina; Ioana, Cornel; Mansour, Ali (Frontiers in Signal Processing, 2023)
Signal modulation identification is of high interest for applications in military communications, but not only. Some possible applications are related to spectrum surveillance, electronic warfare, quality services and cognitive radio. To distinguish between multi-carrier signals, such as Orthogonal Frequency Division Multiplexing (OFDM) signals, and single carrier signals is very important in several applications. Conventional methods face a stalemate in which the classification accuracy process is limited and, therefore, new descriptors are needed to complement the existing ones. Another drawback is that some of its features cannot be extracted using conventional feature extraction techniques in practical OFDM systems. This paper introduces a new signal detection algorithm based on the phase diagram characterization. Firstly, the proposed algorithm is described and implemented for simulated signals, in MATLAB. Secondly, the algorithm performance is verified in an experimental scenario by using Long Term Evolution OFDM signals over a software defined radio (SDR) frequency testbed. Our findings suggest that the algorithm provides good detection performance in realistic noisy environments.